Association between dietary consumption of multiple vitamins and age-related macular degeneration: a cross-sectional observational study in the National Health and Nutrition Examination Survey 2005–2008 - Liu, Zhao; Wang, Qiuyuan; Li, Lu; Cai, ShanJun (Frontiers in Nutrition, 2024)
Purpose Age-related macular degeneration (AMD) is one of the common causes of blindness in the elderly worldwide. Its prevention and monitoring indicators remain a key area of research. This study aims to examine the association between vitamin intake and AMD prevalence. Methods Data from the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2008 were used for cross-sectional analysis. Logistic regression models, subgroup analyses and multicollinearity regression were employed to assess the association between vitamin intake and AMD. Results A total of 1,627 participants were included, with 54.5% (weighted) males and 45.5% (weighted) females. Significant differences were observed in the intake of vitamins B (B1, B2, B6, and B12), E, and folic acid between the AMD and Non-AMD groups. The Non-AMD group had higher average intakes (weighted) of vitamin B1 (1.71 ± 1.10 vs. 1.37 ± 0.64), B2 (2.42 ± 1.22 vs. 1.86 ± 0.70), B6 (2.05 ± 1.25 vs. 1.71 ± 0.85), B12 (5.73 ± 6.18 vs. 4.54 ± 3.27), E (7.93 ± 5.47 vs. 6.39 ± 2.86), and folic acid (181.87 ± 178.04 vs. 140.72 ± 124.60). Logistic regression and subgroup analyses further supported these findings. Conclusion This study found that higher vitamin intakes B and E were associated with a lower prevalence of AMD in the U.S. population. Eating a healthy diet rich in vitamins B and E, particularly B2 (eggs, green vegetables, meat, mushrooms, and almonds) may help to reduce vision loss due to AMD. However, since this is a cross-sectional study, causal associations between vitamin intake and AMD cannot be established. Further randomized clinical trials are needed to confirm these findings.